PROTOTYPE DRYER SOLAR IN TERMS OF USAGE DUAL COLLECTOR THERMAL AND SYSTEM PHOTOVOLTAIC - Ridwan, Kiagus Ahmad (KINETIKA, 2018)
Direct drying method is still widely used by the general public and home industry, in the application of this type of method has several disadvantages such as susceptible to dust or pollution so that the resulting product is not hygienic and the drying time up to days is also a shortage of direct drying. Based on the problems faced, an innovation is carried out in the process of drying environmentally friendly food by using thermal collectors and solar panels as a result of renewable energy development. From the results of the study it can be seen that the length of drying time affects the energy produced by the dual collector thermal to the mass of vaporized H2O and the resulting heat loss. In the research carried out, mass H2O was highest evaporated in the 240th minute of 0,1998 grams and the highest amount of heat loss in the 300th minute was 1604,38 kJ with the energy produced by the dual collector thermal was 4221,0498 kJ, whereas in the study with the use of photovoltaic systems the highest amount of heat loss produced in the 120th minute is 570,389 kJ and the highest electrical power generated at 12:00 WIB with a slope of 300 angle of 10,25 watts.